1996
DOI: 10.1063/1.362796
|View full text |Cite
|
Sign up to set email alerts
|

Electronic transport properties of Sr1−xLaxTiO3 ceramics

Abstract: Articles you may be interested inChromium and nickel ion irradiation effects on the low and hightemperature metalsemiconductor transitions in (V1−x Cr x )2O3 ceramics

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
90
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 214 publications
(103 citation statements)
references
References 22 publications
12
90
1
Order By: Relevance
“…S9, ESI †). 35 Above this temperature, σ decreases with increasing T as carrier mobility is reduced with a σ for La0.5Na0.5Ti0.8Nb0.2O3 comparable to that of Sr0.9Dy0.1TiO3-δ measured in this study. Observation of negative thermopowers indicates that the carriers are predominantly n-type in nature, and the absolute magnitudes of S500 K decrease from -22211 to -1276 μV K -1 from x = 0.05 to 0.2 as a result of increasing carrier concentration n (Fig.…”
Section: J Namementioning
confidence: 67%
“…S9, ESI †). 35 Above this temperature, σ decreases with increasing T as carrier mobility is reduced with a σ for La0.5Na0.5Ti0.8Nb0.2O3 comparable to that of Sr0.9Dy0.1TiO3-δ measured in this study. Observation of negative thermopowers indicates that the carriers are predominantly n-type in nature, and the absolute magnitudes of S500 K decrease from -22211 to -1276 μV K -1 from x = 0.05 to 0.2 as a result of increasing carrier concentration n (Fig.…”
Section: J Namementioning
confidence: 67%
“…The power law exponent reported in the literature varies from 1.5-2.7 over a temperature range of 100-1300 K. Tufte et al 25 reported an exponent of 2.7 around 100-400 K. Uematsu et al 26 observed an exponent of 2.0 over a temperature range of 500-1000 K. Moos et al 27 noted a change in the exponent from 2.7 close to room tem- perature to 1.6 above 1000 K. Unlike these observations, Ohta et al 7 reported an exponent of 1.5 over 300-1000 K and correlated the behavior to phonon scattering as observed in classical semiconductors 28 . Previous studies found no dependence of the exponent on the carrier concentration.…”
Section: Galvanomagnetic Propertiesmentioning
confidence: 96%
“…The power of ÀM is intermediate to the reported values: À2:7 to À3:2 at 100-300 K and À1:6 at high temperature. 21,22) Figure 7 shows the temperature dependencies on the thermal conductivity of CSed SLTO. The thermal conductivity decreased with the increasing temperature; this was caused by the decrease in the thermal diffusivity.…”
Section: Dependences Of Temperature and Doping Amount Onmentioning
confidence: 99%